EFEKTIVITAS PROGRAM APLIKASI SAMBARA DALAM PENINGKATAN KUALITAS PELAYANAN PADA SISTEM ADMINISTRASI MANUNGGAL SATU ATAP KOTA BOGOR - Muhammad Rizky Ferdian Juanda; Usep Dayat; Sopyan Resmana Adiarsa (PRAJA: Jurnal Ilmiah Pemerintahan, 2022)
Samsat Mobile West Java (SAMBARA) application is an electronic-based innovation made by BAPENDA West Java whose function is to check Motor Vehicle Tax in West Java Region. The application can display motor vehicle tax information both two-wheeled and four-wheeled in Jabar online. The benefits of this application, checking motor vehicle tax and also to make payment of motor vehicle tax, knowing the schedule of samsat roving and Samsat Gendong (Samdong), and through the Sambara application can also find out the location of Samsat services. In this study researchers used the theory of effectiveness of Sutrisno and indicators of the quality of public services according to De Vreye. And the method used is descriptive qualitative with data collection techniques conducted by researchers is to take data in the library, read, record, and process research materials. With this Sambara application to facilitate and shorten the time for people who will pay taxes so that people no longer have to wait in line when they want to pay motor vehicle tax